Indigenous knowledges in global contexts: Multiple readings of our world - Hall, B.L.; Dei, G.J.S.; Rosenberg, D.G. (University of Toronto Press, 2000)
Indigenous knowledges are understood as the common sense ideas and cultural knowledges of local peoples concerning the everyday realities of living. This definition refers to the epistemic saliency of cultural traditions, values, belief systems and world views that, in any indigenous society, are imparted to the younger generation by community elders. It is also refers to world views that are products of a profoundly direct experience of nature and its relationship with the social world. Bringing new and complex readings to the term 'indigenous', this collection of essays from Canadian and international contributors is an invitation to critically engage in the discussion of indigenous knowledges and their implication for academic decolonization